Association between Serum Ferritin and Goitre in Iranian School Children (Journal of Health, Population and Nutrition, 2010)
Despite long-standing supplementation of iodine in Iran, the prevalence of goitre among general people remains high in some regions. The study investigated the role of iron status in the aetiology of goitre in school children in Isfahan, Iran. Two thousand three hundred and thirty-one school children were selected by multi-stage random sampling. Thyroid size was estimated by inspection and palpation. Urinary iodine concentration (UIC) and serum ferritin (SF) were measured. Overall, 32.9% of the children had goitre. The median UIC was 195.5 μg/L. The mean±SD of SF in the goitrous and non-goitrous children was 47.65±42.51 and 44.55±37.07 μg/L respectively (p=0.52). The prevalence of iron deficiency in goitrous and non-goitrous children was 9.6% and 3.1% respectively (p=0.007). Goitre is still prevalent in school children of Isfahan. However, their median UIC was well in the accepted range. Iron deficiency is associated with goitre in a small group of goitrous children. The role of goitrogens should also be investigated in this region. Key words: Cross-sectional studies; Goitre; Iodine; Iron deficiency; Serum ferritin; Iran DOI: 10.3329/jhpn.v28i2.4883 J Health Popul Nutr 2010 Apr; 28(2): 137-142